(untitled) (Research Journal, 2024)
The issue selected for research is found very interesting and essential for future perspective of the workers of the Tea estate of Ilam. Saving is important for accumulation of capital required to generate future income, enable future consumption and to provide mechanism for managing risks. Saving has positive impact on the economy because funds that are placed in financial assets are their channeled through financial intermediaries to fund investments by firms. High saving leads the accumulation of wealth that allows individuals to improve their living standard. This study focuses on saving behavior of permanent workers of Ilam Tea-estate. The general objectives of the study is find out the present income situation of the workers of Tea-estate and the specific objectives is to analyze saving behavior of their income. Specially, primary data are used in this study. To collect primary data, the researcher used field survey, observation and direct interview method with 15 permanent workers in the Tea-estate. According to the collected data, information’s and direct interview, two variables, financial literacy and self-control have the strong significant on the saving behavior of the workers.